Optimization of drying conditions and components to reduce wall sticking during spray drying of infant formula milk - Lin, Yawen; Liu, Yanhong; Wang, Lu; Xie, Yongkang; Gao, Zhenjiang; Wang, Shaojin (International Journal of Agricultural and Biological Engineering, 2018)
Wall sticking, which greatly reduces productivity and product quality, has been a big challenge of spray drying. Structure of drying tower and atomizer, as well as drying conditions are the main influencing factors. This research explored the possibility to reduce wall sticking by optimizing drying conditions and components to obtain higher recovery rate of powdered infant formula milk (PIFM). Response surface experimental results indicated that inlet air temperature (T), feed concentration (C), feeding speed (S), as well as interaction term of TC and quadratic terms of C2 and S2 had significant influences on recovery rate for determined milk formula. According to mixture experiments at optimized drying conditions, whey protein (P), fat (F) and lactose (L) contents, as well as interaction term FL had significant effects on recovery rate. Positive effects were observed for F and L contents on recovery rate, while negative effects were observed for P and FL. Under the optimized drying condition of 136°C, 19.80% and 4.07 mL/min, respectively, for T, C and S, the maximum recovery rate of 58.98% was obtained for PIFM with P, F and L content of 18%, 31% and 51%, respectively. Wall sticking phenomena could be reduced by optimizing drying conditions and mildly adjusting components of infant formula milk. Keywords: spray drying, drying condition, wall sticking, inlet temperature, feed concentration, feeding speed, powder recovery rate, infant formula milk DOI: 10.25165/j.ijabe.20181102.2788 Citation: Lin Y W, Liu Y H, Wang L, Xie Y K, Gao Z J, Wang S J. Optimization of drying conditions and components to reduce wall sticking during spray drying of infant formula milk. Int J Agric & Biol Eng, 2018; 11(2): 214–218.